The Effects of L-dopa, SCH23390 Hydrochloride and Sulpiride on Adiponectin and Luteinizing Hormone Levels in an Animal Model of Polycystic Ovary Syndrome - Khadijeh Haghighat Gollo; Fariba Mahmoudi; Abolfazl Bayrami; Saber Zahri (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2020)
Background and Aim: In patients suffer from Polycystic Ovary Syndrome (PCOS), the secretion of the Luteinizing Hormone (LH) increases while adiponectin secretion and dopamine release decreases. Dopamine and adiponectin exert inhibitory effecs on LH secretion. In the present study the effects of L-dopa and dopamine receptor antagonists were investigated on LH secretion and adiponectin gene expression of in PCOS model rats to determine whether dopaminergic pathway might be involved in the decreasing LH via affecting adiponectin. Methods & Materials: Following estradiol valerate- induced PCOS, fifteen PCOS rats were divided into 3 groups including saline receiving group, L-dopa(100 mg/kg) or simultaneous injections of sulpride(10 mg/kg), SCH23390 hydrochloride (1 mg/kg) and L-dopa(100 mg/kg), Five intact rats received saline as negative control group. Blood samples were collected via tail vein. Ovary and hypothalamus were dissected and frozen. Serum concentration of LH and relative gene expression of adiponectin in ovary and hypothalamus were determined by radioimmunoassay and real time-PCR method. Ethical Considerations: This study was approved by the Research Committee of University of Mohaghegh Ardabili (Code: 95.125.1). Results: Induction of PCOS caused a significant increase in mean serum concentration of LH and a significant decrease in mean relative gene expression of ovarian and hypothalamic adiponectin compared to control group. L-dopa caused a significant decrease in serum concentration of LH, a significant decrease in hypothalamic gene expression of adiponectin compared to PCOS rats. But it did not significantly increase ovarian adiponectin gene expression in comparison to PCOS rats. Dopamine receptor antagonists inhibit the effects of L-dopa on LH and hypothalamic gene expression of adiponectin. Conclusion: Dopaminergic signaling pathway may be involved in decreasing LH secretion via increasing hypothalamic adiponectin gene expression level in PCOS rats.